Об объекте и предмете библиотековедческих исследований (Библиосфера)
The authors treat different approaches to the definition of object and subject in library science investigations, offer their own definition of the notion «the object of library science investigation» as a library process and come to the conclusion, that the definition of the investigation object and subject should be the obligatory element of its program and the object of library investigation should have a library nature, belong to library science, but not to other sciences; and the subject should make the theme of the investigation more concrete, but not repeat its title.